Correction: Ultrafast dye regeneration in a core–shell NiO–dye–TiO2 mesoporous film. Issue 46 (15th November 2018) - Tian, Lei; Föhlinger, Jens; Pati, Palas Baran; Zhang, Zhibin; Lin, Junzhong; Yang, Wenxing; Johansson, Malin; Kubart, Tomas; Sun, Junliang; Boschloo, Gerrit; Hammarström, Leif; Tian, Haining
Abstract : Correction for 'Ultrafast dye regeneration in a core–shell NiO–dye–TiO2 mesoporous film' by Lei Tian et al., Phys. Chem. Chem. Phys., 2018, 20, 36–40.